Extraction and quantification of anthocyanins from dehydrated Clitorea Ternatea flowers (Research, Society and Development, 2022)
Clitoria ternatea is a perennial plant of the Fabaceae family used mainly as a forage plant. The flowers can be used in human food, highlighting the high content of anthocyanins and high antioxidant capacity. Dehydration is a process of water removal and one of the main ways used in food preservation. This work aims to dehydrate the flower and compare some attributes with those of commercial dehydrated flowers. The flowers were dehydrated for six hours at 50°C in a forced convection hot air dryer, reaching an average final humidity of 8.39%. The dehydrated commercial flower presented moisture of 18.34%. For both samples, the dye hydroalcoholic extract was obtained, which was concentrated and characterized in terms of anthocyanin content. The anthocyanins content of 10.0 mg/100 ml was obtained for the concentrated coloring extracts obtained from the flowers dried by hot air, while for the concentrated extracts of the commercial dehydrated flowers, a value of 5.23 mg/100 ml was obtained. The cultivation of edible flowers has great potential for expansion and new studies on the ways of using such flowers should contribute to the rational development of cultures that are still little explored, such as Clitoria ternatea, with more studies in the search for solutions to problems such as improving stability and shelf life through drying.